'Incomparabilissime Fabrice': The Architectural History of Salisbury Cathedral c. 1297 to 1548. (1st September 2013) - Tatton-Brown, Tim; Lepine, David; Saul, Nigel
Abstract : Salisbury cathedral is usually seen as a 'one period' building, a 'complete' 13th-century cathedral. As a result, the later medieval work at Salisbury has rarely been considered in its own right. This neglect has been compounded by the subsequent loss of many of its most important elements: the two eastern chantry chapels, St Osmund's shrine and half the library. The aim of this paper is to redress this imbalance. Salisbury's original appearance was transformed dramatically in the early 14th century by the construction of the high tower and spire, and in the later 15th century, following the canonisation of St Osmund, when the east end was substantially remodelled. As at other great churches, the interior was continuously adapted to enable the cathedral to meet the spiritual needs of late medieval society. These were principally the performance of the liturgy, the commemoration of the dead, the augmentation of devotional cults and the promotion of learning. These themes are explored in the discussion of the new library, major monuments, the shrine of St Osmund and the construction of four new chantry chapels. Thus the cathedral evolved significantly in the two and a half centuries after Bishop Ghent's consecration in 1297.